VARIABEL-VARIABEL YANG MEMPENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG PUBLIK - DEWI SARI WIJOYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This research is conducted to analyze the influence of public ownership, firm size, profitability, industrial sector, audit quality and financial leverage toward income smoothing practice among manufacturing companies listed in Indonesia Stock Exchange. The sample of this research consisting of 235 data that have been listed in Indonesia Stock Exchange during period 2007 until 2011 that have been selected by using purposive sampling method. The hypothesis were tested by using binary logistic regression. The empirical result indicates that profitability and audit quality have a positive effect on income smoothing. However, this study doesn’t show any influence among public ownership, firm size, industrial sector and financial leverage toward income smoothing practice.